2011
DOI: 10.1097/cad.0b013e328349597d
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G2/M phase arrest and apoptosis by potent antitumor APCA in human cervix carcinoma cells

Abstract: 3-(dimethylamino-ethylamino)-8-oxo-8H-acenaphthol[1, 2-b]pyrrole-9-carboxylic acid (APCA), as a potent antitumor compound, showed anticancer activity on a series of established cancer cells. Meanwhile, the cytotoxic effects of APCA were much smaller on normal human cells than that on cancer cells. This study investigated the molecular mechanisms underlying APCA-induced growth inhibition in HeLa cells. The results showed that the APCA-induced cell cycle arrest at G(2)/M phase correlated with cyclinB1 and cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The cyclinB1/Cdk1 complex is the primary regulator of the transition from G 2 to M phase [26]. Without synthesis of cyclinB1 before the G 2 /M transition, Cdk1 remains inactive, and the cell cannot enter mitosis, resulting in cell cycle arrest at the G 2 phase [27]. Our data suggests that SULT2B1b inhibition in Hepa1-6 cells can cause G 2 /M phase arrest by decreasing cyclinB1 transcript levels and decreasing its protein stability.…”
Section: Discussionmentioning
confidence: 72%
“…The cyclinB1/Cdk1 complex is the primary regulator of the transition from G 2 to M phase [26]. Without synthesis of cyclinB1 before the G 2 /M transition, Cdk1 remains inactive, and the cell cannot enter mitosis, resulting in cell cycle arrest at the G 2 phase [27]. Our data suggests that SULT2B1b inhibition in Hepa1-6 cells can cause G 2 /M phase arrest by decreasing cyclinB1 transcript levels and decreasing its protein stability.…”
Section: Discussionmentioning
confidence: 72%
“…The cyclinB1/Cdk1 complex is the primary regulator of the transition from G2 to M phase [36]. Without synthesis of cyclinB1 before the G2/M transition, Cdk1 remains inactive, and the cell cannot enter mitosis, resulting in cell cycle arrest at the G2 phase [37]. Our data suggests that MT-1X inhibition in HepG2 cells can cause G2/M phase arrest by decreasing its protein level.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, further investigation showed that BND‐12 could only induce HepG2 cells apoptosis via intrinsic mitochondrial pathway, but not necrosis or autophagy. Based on many naphthalimide derivates, induced tumour cell apoptosis via caspase 3 and caspase 9 activation, mitochondrial pathway‐mediated cell apoptosis may be a main antitumour mechanism for naphthalimide derivates [11] . In our previous study, a novel amonafide analogue NPC‐16 not only induced HepG2 cell apoptosis but also autophagy [12] .…”
Section: Discussionmentioning
confidence: 89%
“…Based on many naphthalimide derivates, induced tumour cell apoptosis via caspase 3 and caspase 9 activation, mitochondrial pathway-mediated cell apoptosis may be a main antitumour mechanism for naphthalimide derivates. [11] In our previous study, a novel amonafide analogue NPC-16 not only induced HepG2 cell apoptosis but also autophagy. [12] Whereas, Quaquebeke et al [14] reported that a naphthalimide derivative notably induced tumour cell autophagy and senescence, but not apoptosis.…”
Section: Bnd-12 Tumour Growth and Metastasismentioning
confidence: 89%
See 1 more Smart Citation